Kebebasan Pers Dan Pencegahan Ujaran Kebencian: Telaah Yuridis Atas Undang- Undang Nomor 40 Tahun 1999 Tentang Pers - Gun Ramajayadi; Reftahul Janna; Ayu Putriyana (GLOBAL SCIENTS PUBLISHER, 2025)
This research examines the effectiveness of Law Number 40 of 1999 on the Press in guaranteeing press freedom while simultaneously preventing the misuse of media as a vehicle for spreading hate speech. Press freedom is recognized as one of the pillars of democracy, yet in practice it often faces ambiguity, particularly in distinguishing legitimate criticism from hate speech. Using a normative juridical approach, this study analyzes the legal norms contained in the Press Law, its relation to other regulations such as the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), as well as law enforcement practices in Indonesia. The findings indicate that although the Press Law provides substantial legal protection for freedom of expression, law enforcement remains inconsistent and often creates the potential for criminalization of the press. The overlap of regulations and ambiguity in interpretation result in legal uncertainty and weaken the role of the press as a means of social control. Therefore, this research emphasizes the need for regulatory harmonization, strengthening the role of the Press Council, and applying the principle of proportionality in law enforcement to ensure that press freedom is preserved without neglecting the effort to prevent hate speech.